Workload and injury incidence in elite football academy players - Delecroix, B.; Delaval, B.; Dawson, B.; Berthoin, S.; Dupont, G. (Journal of Sports Sciences, 2019)
he aim of this study was to prospectively analyse the relationship between workloads and injury in elite football academy players. Elite football academy players (n = 122) from under-19 (U19) and under-21 (U21) of a professional football team competing in UEFA European Cups were followed during 5 seasons. Injuries were collected and absolute workload and workload ratios (4-weeks, 3-weeks, 2-weeks and week-to-week) calculated using a rolling days method with the help of the session Rate of Perceived Exertion. There was no association between absolute workload or workload ratio with the injury incidence in the U19. In the U21, the level of cumulative absolute workloads during 3-weeks (RR = 1.39, p = 0.026) and during 4-weeks (RR = 1.40, p = 0.019) were associated with an increase in injury. There was no association between workload ratio and injury in U21. The significant link between high cumulated 3-weeks and 4 weeks workloads and injury in U21 confirmed the requirement to monitor the internal subjective workload in U21 in order to prevent injury. Further studies exploring the relationships between workload and injury are required in football academy.